Effects of heat treatment on the shape recovery of selective-laser melted NiTi - Lee, Dennis Ying Le (2018)
The complexity in conventionally manufacturing NiTi has led to the additive manufacturing of NiTi with Selective Laser Melting (SLM). Considering the importance of the shape memory properties in Nitinol, it is therefore essential to investigate ways to improve it in SLM printed NiTi samples. In the project, the NiTi samples were produced by melting NiTi powder (50.16 .at% Ni, 49.84 .at% Ti) using SLM. The samples were subjected to rapid annealing for 5 minutes at different heat treatment temperatures: 400 ⁰C, 500 ⁰C, 600 ⁰C and 700 ⁰C. It was observed that the sample heat treated at 400 ⁰C showed the greatest transformation strain and shape recovery. The ASTM Grain Size Number was also observed to decrease with increasing annealing temperature. Differential Scanning Calorimetry (DSC) was used to determine the phase transformation temperatures for the NiTi samples. The DSC curves showed two peaks in proximity for both the cooling and heating cycles, suggesting the absence of the intermediate R-phase. The two peaks in the DSC curves were attributed to the two-step SLM process and it was concluded that cooling time for affects the extent of solidification for SLM NiTi. Energy-Dispersive X-ray Spectroscopy and X-Ray Diffraction confirmed the existence of the Ti2Ni precipitates in the NiTi samples.